INFLUENCE OF DISCOVERY BASED LEARNING LEARNING MODEL WITH SCIENTIFIC APPROACHON LEARNING OUTCOMES - Syarifuddin; Deni Iriyadi; Yuddin (LPPM Universitas Negeri Jakarta, 2019)
This study aims to determine the comparison of mathematics learning outcomes of students in grade VIII SMP which is taught through Discovery based learning learning by using Scientific approach on Opportunity material. The type of this research is Experimental Research. The subject of this study is the students of class VIII SMP in the even semester of the academic year 2014/2015 which amounted to 40 people. The data collected consisted of data on student learning outcomes and student response data on the device and learning. Data were analyzed using descriptive analysis and inferential analysis. Descriptive research results data show the results of student learning taught by learning model Discovery based learning using scientific approach is in the high category with an average of 82.42 with a standard deviation of 6.09 from ideal score 100. Average value of the gain of 0.75 with a standard deviation of 0.06 from ideal score 1 is in the high category, and classical learning completeness of 87.5%, while student response is in the category tends to positive with an average of 3.29. Descriptively mastery of learning outcomes and student responses are different. Hypothesis testing of differences in learning outcomes was done with the help of SPSS 20 for significant learning outcomes with α = 0.05 and for significant normalized gain values with α = 0.05. So it can be concluded that there is an influence on student learning outcomes taught through discovery based learning learning model.